Production of FucoPol by Enterobacter A47 using waste tomato paste by-product as sole carbon source. (March 2017) - Antunes, Sílvia; Freitas, Filomena; Sevrin, Chantal; Grandfils, Christian; Reis, Maria A.M.
Highlights: Enterobacter A47 was cultivated on tomato paste by-product as sole carbon source. Tomato paste supported cell growth and was used for exopolysaccharide synthesis. High volumetric productivity was reached with continuous substrate feeding. Tomato paste was successfully valorized into FucoPol. Abstract: Out-of-specification tomato paste, a by-product from the tomato processing industry, was used as the sole substrate for cultivation of the bacterium Enterobacter A47 and production of FucoPol, a value-added fucose-rich extracellular polysaccharide. Among the different tested fed-batch strategies, pH-stat, DO-stat and continuous substrate feeding, the highest production (8.77 g L −1 ) and overall volumetric productivity (2.92 g L −1  d −1 ) were obtained with continuous substrate feeding at a constant flow rate of 11 g h −1 . The polymer produced had the typical FucoPol composition (37 mol% fucose, 27 mol% galactose, 23 mol% glucose and 12 mol% glucuronic acid, with an acyl groups content of 13 wt%). The average molecular weight was 4.4 × 10 6  Da and the polydispersity index was 1.2. This study demonstrated that out-of-specification tomato paste is a suitable low-cost substrate for the production of FucoPol, thus providing a route for the valorization of this by-product into a high-value microbial product.